Development and validation of a 3D vibrating contact probe for micro-CMMs - Claverley, James David (2014)
The state-of-the-art in dimensional metrology in terms of accuracy and 3D measurement is the micro-co-ordinate measuring machine, or micro-CMM. Current manufacturing trends are inclined towards miniaturisation, and all developments in this area are dependent on the capabilities of dimensional metrologists. Currently, the main limiting factor in the advancement of co-ordinate metrology at the micrometre scale is the design, manufacture and resulting accuracy of contacting micro-CMM probes. With this in mind, this thesis describes the development of a novel 3D vibrating micro-CMM probe. The main contributions of this thesis are as follows.